Respuestas

¡La mejor respuesta!
2012-06-29T03:20:30+02:00

  2                                                                                2
x   -    6  <  0                 2x + 3 = 0                        (-3/2)   - 6  
   2x+3                              x= -3                              -9/4 - 6  
                                             2                              -9-24  =  -32/24= -16/12=-8/6 =-4/3
                                                                                24